High fluoride incidence in groundwater and its potential health effects in parts of Sarguja Area Chhattisgarh, India - Upadhay, Manish (Recent Research in Science and Technology, 2013)
<span style="font-size: 10.0pt; line-height: 115%; font-family: "Arial Narrow","sans-serif"; mso-fareast-font-family: BatangChe; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-fareast-language: KO; mso-bidi-font-weight: bold;">Assay of fluoride concentration in ground water samples around Surajpur district in Sarguja revealed that fluoride content in beyond the permissible limit in a some residential areas. The extent of Fluoride present in different samples was obtained by spectrophotometer. the extent of fluoride was found in village Baraul found to be from minimum 2.4 to 3.0 mg/l. village Ramtirath found to be from minimum 2.1 to 3.0 mg/l. but in village Fatehpur and Barwahi found to be from minimum 2.1 to 3.50 mg/l. it is further added that extent of fluoride content in water depends on the climatic conditions and increase in summer.